The correct formulation of clinical questions for the practice of evidence based medicine. - Carneiro, A V (Acta Médica Portuguesa, 1998)
Evidence-based medicine is the conscientious, explicit, and judicious use of the best evidence available to make decisions about the care of individual patients. The practice of EBM means integrating individual clinical expertise with the best available external clinical evidence from systematic research. The good practice of EBM begins with a well formulated clinical question, meaning that it should be clear, directly relevant to the problem at hand and answerable by searching in medical literature. This paper begins by presenting the central tasks of clinical work from which clinical questions arise. The components of well formulated clinical questions are then presented. Finally, some of the steps for the correct formulation of questions are discussed.